Consumer Behavior Towards Purchase Intention of Seafood Processed Products in The Province of West Nusa Tenggara - Zulkieflimansyah; Nurjihadi, Muhammad; Mandasari, Jayanti; Levia Tryana, Ayu; Aprirachman, Rozzy (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to analyze the variables that influence purchasing decisions for processed marine products in the Province of West Nusa Tenggara. Determination of the number of respondents who will be the sample using the 10% Margin of Error (MOE) method with a total of 100 respondents consisting of several districts in West Nusa Tenggara Province. The analytical tool used in this research is Multiple Linear Regression to see the relationship between the independent variable and the dependent variable. The research was conducted using a Likert scale on each research variable with ordinal data and transformed into intervals using the  Method Successive Interval (MSI), using the MS.excel application, while the Multiple Linear Regression data processing used the Stata application. The result of this research is that the consumer behavior of processed seafood in West Nusa Tenggara Province is slightly different from the conventional theory of consumer behavior, where the brand has a negative effect on purchasing decisions of 0.2129039 points, and convenience has a negative effect on purchasing decisions of 0.1199636 points. Meanwhile, price, packaging, promotion, benefits, and consumer traditions have a positive effect on purchase intention. Processed seafood products in West Nusa Tenggara Province have different consumer characteristics from other products in general.